Magnitude and Factors Associated with Teenage Pregnancy in Somaliland: Evidence from Somaliland Health and Demographic Survey, 2020 - Gensa Geta T; Ahmed Abdiwali S; Farah MM (Dove Medical Press, 2023)
Teshome Gensa Geta,1,2 Saad Ahmed Abdiwali,2 Mustafe Mohamoud Farah3 1Department of Public Health, College of Medicine and Health Science, Wolkite University, Wolkite, Ethiopia; 2Department of Public Health, School of Medicine and Health Sciences, Gollis University, Hargeisa, Somaliland; 3Department of Nutrition, School of Medicine and Health Sciences, Gollis University, Hargeisa, SomalilandCorrespondence: Teshome Gensa Geta, Tel +251910686501, Email teshgen2006@gmail.comPurpose: Teenage pregnancy is estimated to be common in Somaliland. It is linked with adverse perinatal outcomes. However, no study has been conducted in the country on this subject. Therefore, this study intended to assess the magnitude and factors associated with teenage pregnancy in Somaliland.Patients and Methods: Data from the 2020 Somaliland Health and Demographic Survey (SLHDS); were used in the current analysis. A total sample of 3,786 women in reproductive age groups were involved as participants. The survey used a two-level cluster sampling design, which included initial selection of enumeration areas followed by selection of households. To identify associated factors, binary logistic regression analysis was applied.Results: The magnitude of teenage pregnancy was 47.2% (95%CI: 45.5- 48.9%). Being a nomadic resident (AOR: 1.26; 95%CI: 1.12- 1.71), being in the lowest wealth quintiles (AOR: 1.34; 95%CI: 1.01- 1.77), being in the Sanaag region (AOR: 1.95;95%CI: 1.54- 2.46) and having lower educational attainment (AOR: 2.29; 95%CI: 1.08-4.83) were significantly associated with teenage pregnancy.Conclusion: Teenage pregnancy is highly prevalent in Somaliland and associated with a lower educational level, lower wealth quintiles and nomadic residence. Hence, governmental and non-governmental organizations should work on educating and financially empowering women by giving particular focus to nomadic people.Keywords: teenage pregnancy, associated factors, Somaliland, Magnitude